A Bayesian analysis of white dwarfs in open clusters observed with Gaia. Issue Volume 15:Issue S357(2019) (October 2019) - Jeffery, Elizabeth J.; von Hippel, Ted; Robinson, Elliot; van Dyk, David; Stenning, David
Abstract: We analyze individual white dwarfs in open clusters observed by Gaia. In particular, we determine ages when different model ingredients are used. We also explore fundamental properties of the white dwarfs, including temperature and mass, when using different filter combinations. Such tests are important to understanding any systematic effects when applying similar techniques to field stars.